Regulation by cAMP and vasoactive intestinal peptide of phosphorylation of specific proteins in striatal cells in culture. - Girault, J A (1988)
We have studied three low molecular weight phosphoproteins, ARPP-16, ARPP-19, and ARPP-21 (cAMP-regulated phosphoproteins of Mr 16,000, 19,000, and 21,000, respectively) in reaggregate cultures from various regions of fetal mouse brain. ARPP-16 and ARPP-21 were detected only in striatal and cortical cultures. In contrast, ARP-19, which is structurally related to ARPP-16, was also present in reaggregate cultures prepared from thalamus and ventral and dorsal mesencephalon, as well as in monolayer cultures of astroglial cells. In striatal aggregates cultured over a 3-week period, the relative levels of ARPP-16, ARPP-21, and synapsin I/protein IIIa (synaptic vesicle-associated phosphoproteins closely related to each other and treated as a single entity in the present study) increased with time, whereas the level of ARPP-19 decreased. Incubation of striatal aggregates with 8-Br-cAMP, forskolin, or vasoactive intestinal peptide increased the phosphorylation of all these proteins. We conclude that the state of phosphorylation of two proteins enriched in specific neurons (ARPP-16 and ARPP-21) and two more widely distributed proteins (ARPP-19 and synapsin I/protein IIIa) is regulated by cAMP and vasoactive intestinal peptide in striatal cells in culture. These phosphoproteins may therefore play a role in mediating some of the actions of vasoactive intestinal peptide in the caudate-putamen.